THE INFLUENCE OF THE SELECTED INTERNATIONAL ORGANIZATIONS ON THE DEVELOPMENT OF TRANSPORT - Maciej MINDUR; Leszek MINDUR (Scientific Journal of Silesian University of Technology. Series Transport)
An important role in the effective functioning and promotion of transport is played not only by transport and forwarding companies, but also by non-governmental organizations, closely cooperating with the industry and representing them in decision-making bodies. The article presents selected organizations representing the transport sector at the global and community forums. The analysis covers the influence of these organizations on establishing international law, unifying technical, organizational, operational and economic solutions, and the preparation of shipping documents. The activities aimed at standardization and unification of land transport for the purposes of intermodal transport were also discussed.